Quality of the Relationship Coach-Athlete and Goal Orientation as Predictors of Sport Performance - Vieira, José Luiz Lopes (2017)
This study investigated the quality of the coach-athlete relationship (CAR) and goal orientation (GO) as predictors of sport performance in volleyball players. Participants (n=185) completed the Coach-Athlete Relationship Questionnaire and the Task and Ego Orientation in Sport Questionnaire. The medalists perceived greater closeness and commitment to the coach and greater task orientation (TO) compared to non medalists. The CAR showed moderate impact on TO among medalists and male athletes (proximity and complementarity) as well as among non-medalists and female athletes (commitment). Commitment showed moderate effect on the ego orientation of non-medalists and women (not significant). It is concluded that the higher the performance level of the teams, the higher the influence of CAR (complementarity and proximity) on TO.